Main Points in the Lexicological Studies on “Blessing” in the Old Testament - Grigorova, Kalina (Forum Theologicum Sardicense, 2025)
Kalina Sl. Grigorova, Main Points in the Lexicological Studies on “Blessing” in the Old Testament. This paper provides a brief critical overview of lexicological studies on “bless-ings” in the Old Testament within Western Christian (mainly Protestant) theological publications from the early twentieth century to the end of the second decade of the twenty-first century. These studies focus primarily on the root brk. The paper presents the results of a frequency analysis of the derivatives of the brk root in the Old Testament text. Additionally, it draws conclusions based on the research findings and suggests discussion points for further study.